Effect of surfaces roughness of a staggered tube bank in cross flow with air on heat transfer and pressure drop. (March 2023) - Karali, Mohamed A.; Almohammadi, Bandar Awadh; Bin Mahfouz, Abdullah S.; Abdelmohimen, Mostafa A.H.; Attia, El-Awady; Refaey, H.A.
Abstract: Many options are devoted to enhancing heat transfer alongside lowering the pressure drop inside the tube banks in cross flow with air. Among these, is attaching splitter plates (SPs) to the trailing edges of the tubes as extended surfaces. That already proved from literature its effective use. Another proposed option is to increase the surface's roughness, with limited available data from literature. Thus, the present research was established to study the effect of using different surface roughness of a staggered tube-bank in cross flow with air on heat transferred and pressure drop besides the comparison with installing SPs. To this aim, a full 3D CFD model is developed to study the two mentioned options without any symmetrical boundary conditions. The study extended to include the effect of Remax changes from 5000 to 100, 000. While three surface relative roughness; ks /D = 0 (smooth), ks /D = 0.01, and ks /D = 0.02 are investigated. The results confirmed that increasing heat transfer surface roughness helps to augment the total heat transferred. While a limited pressure drop increase is reported compared to installing SPs. Combining both; increasing surface roughness, and, adding SPs, led to multiplying the total heat transfer rate.